REPRODUCTIVE PLANNING AND INSERTION OF INTRAUTERINE DEVICES BY PHYSICIANS AND NURSES IN BRAZIL - Rodrigues, Gabrielle Almeida; Alves, Valdecyr Herdy; Rodrigues, Diego Pereira; Pereira, Audrey Vidal; Marchiori, Giovanna Rosario Soanno; Oliveira, Maria Luiza Bezerra; Costa, Dannyelly Dayane Alves da Silva (Cogitare Enfermagem, 2023)
Objective: to analyze the records referring to reproductive planning consultations and to intrauterine device insertion performed in 2021 by nurses and physicians in Primary Health Care in Brazil. Method: this is a quantitative, cross-sectional and descriptive study that resorted to secondary data from the Health Information System for Primary Care and submitted to simple descriptive statistics data analysis. Results: a total of 18,243 procedures about IUD insertion were recorded in the country, with prevalence of physicians, except for the state of Roraima; as well as 54,186 reproductive planning consultations with predominance of 41,184 (76%) nurses in relation to physicians (13,002; 24%). Conclusion: there is a need to invest in the training of physicians and nurses in order to expand access and the right to sexual life care of the women living in the country. Nursing care is a way to consolidate women's right to sexual and reproductive life care.